Neural Function Before and After Mindfulness-Based Cognitive Therapy in Anxious Adolescents at Risk for Developing Bipolar Disorder. - Strawn, Jeffrey R.; Cotton, Sian; Luberto, Christina M.; Patino, L. Rodrigo; Stahl, Lauren A.; Weber, Wade A.; Eliassen, James C.; Sears, Richard; DelBello, Melissa P. (Journal of Child & Adolescent Psychopharmacology, 2016)
Objective: We sought to evaluate the neurophysiology of mindfulness-based cognitive therapy for children (MBCT-C) in youth with generalized, social, and/or separation anxiety disorder who were at risk for developing bipolar disorder.Methods: Nine youth (mean age: 13 ± 2 years) with a generalized, social, and/or separation anxiety disorder and a parent with bipolar disorder completed functional magnetic resonance imaging (fMRI) while performing a continuous processing task with emotional and neutral distractors (CPT-END) prior to and following 12 weeks of MBCT-C.Results: MBCT-C was associated with increases in activation of the bilateral insula, lentiform nucleus, and thalamus, as well as the left anterior cingulate while viewing emotional stimuli during the CPT-END, and decreases in anxiety were correlated with change in activation in the bilateral insula and anterior cingulate during the viewing of emotional stimuli (p < 0.05, uncorrected; p < 0.005 corrected; cluster size, 37 voxels).Conclusions: MBCT-C treatment in anxious youth with a familial history of bipolar disorder is associated with increased activation of brain structures that subserve interoception and the processing of internal stimuli-functions that are ostensibly improved by this treatment.